Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Informasi Akuntansi Berbasis E-Commerce pada UMKM (Studi Kasus pada Usaha Mikro, Kecil, dan Menengah di Kabupaten Wonogiri) - Sulistya Sulistya; Rohwiyati Rohwiyati; Indrian Supheni (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
MSMEs are one of the business pillars that have an important role in the ‎Indonesian economy as evidenced by their contribution to GDP of 61.07% or ‎equivalent to 8,573.89 trillion rupiahs. In this all-digital era, MSME activities are ‎already using e-commerce in the transaction process. One of the things that affect ‎the performance of MSMEs is the recording of financial accounting related to ‎business decision-making such as investment and so on. Accounting knowledge, ‎business scale, and education level of MSME business owners are factors that ‎influence the use of e-commerce-based accounting information in MSMEs. The purpose of this ‎study was to find out the influence of knowledge, business scale, and level of ‎education on the use of e-commerce-based accounting information in MSMEs. ‎The data analysis method used was multiple linear analysis with a sample of ‎MSMEs that have used e-commerce-based accounting information in Wonogiri ‎Regency. The results obtained were the significance value of accounting ‎knowledge was 0.006 <0.05, which means this variable had a significant and ‎positive influence on the use of e-commerce-based accounting information. The ‎significance value of the business scale was 0.000 <0.05, which means this ‎variable had a significant and positive influence on the use of e-commerce-based ‎accounting information. The significance value of education level was 0.000 ‎‎<0.05, which means this variable had a significant and positive influence on the ‎use of e-commerce-based accounting information. The conclusion obtained is that ‎the three variables, namely accounting knowledge, business scale, and level of ‎education had a significant and simultaneous influence on the use of e-commerce-‎based accounting information with a significance value of 0.000 <0.05.‎